On Proportional Hybrid Operators in the Discrete Setting - Lizama-Yanez, C (John Wiley and Sons Ltd, 2025)
In this article, we introduce a new nonlocal operator (Formula presented.) defined as a linear combination of the discrete fractional Caputo operator and the fractional sum operator. A new dual operator (Formula presented.) is also introduced by replacing the discrete fractional Caputo operator with the discrete fractional Riemann–Liouville operator. It is shown that it corresponds to a natural discretization of a proportional hybrid operator defined by the Riemann–Liouville operator instead of Caputo hybrid operator. We then analyze the most important properties of these operators, such as their inverse operator and the (Formula presented.) -transform, among others. As an application, we solve difference equations equipped with these operators and obtain explicit solutions for them in terms of trivariate Mittag-Leffler sequences. © 2024 The Author(s). Mathematical Methods in the Applied Sciences published by John Wiley & Sons Ltd.
Keywords: fractional Caputo and Riemann-Liouville operators; Laplace; discrete Laplace; and Poisson transformation; Mittag-Leffler functions and sequences; proportional hybrid operators; Toeplitz operators